Kotobee-Assisted Means-End Analysis Learning: Impact on Algebraic Reasoning Abilities Reviewed From Students' Cognitive Stage - Aflich Yusnita Fitrianna; Anik Yuliani; Anisatul Farida; Nor Syazwani Mohd Rasid (Universitas Syiah Kuala, 2024)
The Indonesian curriculum emphasizes tailored learning based on students' developmental stages and achievement levels, focusing on cognitive development, particularly in algebraic reasoning, which is very important for students' overall cognitive maturation. This study aimed to determine the effect of the implementation of the learning model and students' cognitive stage on algebraic reasoning ability. The study was conducted using quantitative research with a post-test design to achieve the research objective. Two classes were taken as samples from one of the high schools in West Bandung Regency. The instruments used were the Test of Logical Thinking (TOLT) to categorize students into students' cognitive stage groups and algebraic reasoning test instruments to determine the achievement of algebraic reasoning ability. Data analysis was done using statistical tests, including a normality test, homogeneity test, and two-way ANOVA test. The results are: there is an effect of implementing the Means-End Analysis (MEA) learning model supported by Kotobee on algebraic reasoning; there is an effect of students' cognitive stage on algebraic reasoning; and there is no interaction effect of students' cognitive stage and implementation learning model on algebraic reasoning ability. Further research on other mathematical skills using the Kotobee-based MEA learning model is needed.